2021
DOI: 10.1186/s13018-021-02266-z
|View full text |Cite
|
Sign up to set email alerts
|

Tips and tricks to achieve osteotomy healing and prevent refracture after ulnar shortening osteotomy

Abstract: Background Parallel osteotomy is essential for favorable osteotomy reduction and healing and technically challenging during diaphyseal ulnar shortening osteotomy (USO). This study aimed to evaluate the advantages of guided osteotomy for parallel osteotomy and reduction osteotomies, healing over freehand osteotomy. It also aimed to identify surgical factors affecting healing after diaphyseal USO. Methods Between June 2005 and March 2016, 136 wrists … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…While 94 of the 96 plates that were removed in the first year after USO did not lead to refracture, early removal should be performed with caution. While a previous study reported that union is achieved after a mean of 4 to 5 months after USO, complete consolidation was only seen on radiographs after 16 to 20 months (Kang et al., 2021). Therefore, the ulna may be still at greater risk of refracture in the face of a new injury.…”
Section: Discussionmentioning
confidence: 94%
“…While 94 of the 96 plates that were removed in the first year after USO did not lead to refracture, early removal should be performed with caution. While a previous study reported that union is achieved after a mean of 4 to 5 months after USO, complete consolidation was only seen on radiographs after 16 to 20 months (Kang et al., 2021). Therefore, the ulna may be still at greater risk of refracture in the face of a new injury.…”
Section: Discussionmentioning
confidence: 94%